(untitled) (Research, Society and Development, 2021)
The objective of this work was to evaluate seedlings quality of the tree species Agonandra brasiliensis under different doses of the controlled release fertilizer (CRF) Osmocote® and recipient volumes. The experiment was set up in a factorial design for two recipient volumes (1.8 L and 2.2 L) and five CRF doses (0.0; 0.5; 1.0; 2.0; and 3.0 g L-1 of substrate). Four repetitions of one plant each were used. After transplanting seedlings, stem height, stem collar diameter, and the robustness index (RI) were measured in a monthly basis during eight months. The highest seedlings growth was observed with the CRF Osmocote® dose of 2.0 g L-1 and recipients of 2.2 L. The treatment with CRF dose of 2.0 g L-1 in 240 days presented higher initial accumulated growth in height of A. brasiliensis seedlings (mean = 31.38 cm). Seedlings under the dose of 2.0 g L-1 presented 85.90% increase of stem height in relation to the control (substrate without CRF). CRF Osmocote® had positive effect on growth of A. brasiliensis seedlings. Growth was influenced by the different CRF doses and recipient volumes, both for the variables stem height and stem collar diameter and for the RI. The dose 2.0 g L-1 allowed greater accumulated growth in height and diameter in 240 days.